Meson electromagnetic form factors - Dubničková Anna Z.; Dubnička Stanislav (EPJ Web of Conferences, 2012)
The electromagnetic structure of the pseudoscalar meson nonet is completely described by the sophisticated Unitary&Analytic model, respecting all known theoretical properties of the corresponding form factors.